2001
DOI: 10.1159/000056106
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Taurine on Cerulein-Induced Acute Pancreatitis in the Rat

Abstract: Taurine, or 2-aminoethane sulfonic acid, is an intracellular amino acid and has been suggested to have a function in protecting biological systems from oxidative tissue damage. The aim of this study was to determine the effect of taurine against cerulein-induced acute pancreatitis in rats. Acute pancreatitis was induced by administering three subcutaneous injections of cerulein (40 µg/kg body weight) at 1-hour intervals, while taurine was administered intravenously at graded doses (30, 100, or 300 mg/kg, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0
2

Year Published

2002
2002
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 27 publications
2
16
0
2
Order By: Relevance
“…Taurine has been shown to possess significant antiinflammatory properties in various in vivo and in vitro models of inflammation [17]. In TNBS-induced inflammatory bowel disease [6] and cerulein-induced pancreatitis [7], exogenous taurine protected the tissues by increasing the defending capacity of organs against oxidative damage. Similarly, it has been reported that the protective effect of taurine against indomethacin-induced gastric mucosal injury was a direct result of its antioxidant effects which inhibited lipid peroxidation and neutrophil activation [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taurine has been shown to possess significant antiinflammatory properties in various in vivo and in vitro models of inflammation [17]. In TNBS-induced inflammatory bowel disease [6] and cerulein-induced pancreatitis [7], exogenous taurine protected the tissues by increasing the defending capacity of organs against oxidative damage. Similarly, it has been reported that the protective effect of taurine against indomethacin-induced gastric mucosal injury was a direct result of its antioxidant effects which inhibited lipid peroxidation and neutrophil activation [5].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been suggested that the beneficial effect of taurine against indomethacin-induced gastric mucosal damage was due to its antioxidant effects through inhibition of lipid peroxidation and neutrophil activation [5]. In addition, exogenous taurine reduced the inflammatory responses in trinitrobenzene sulfonic acid (TNBS)-induced colitis [6] and cerulein-induced pancreatitis in rats by preventing the production of oxygen free radicals [7].…”
Section: Introductionmentioning
confidence: 99%
“…An inflammatory cascade has been implicated in the pathogenesis of acute pancreatitis (Ahn et al, 2001;Mikawa et al, 2001). TNF-␣ is detected in plasma early in the course of acute pancreatitis, and pretreatment of rats with antibodies raised against the inflammatory cytokine reduces elevated serum amylase in acute pancreatitis (Demols et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…It plays important roles in numerous physiological functions including conjugation with bile acids, modulation of calcium levels, and maintenance of osmolarity, antioxidation and stabilization of membranes [3] . It was reported to have beneficial effects in various physiological and pathological conditions [4][5][6][7] by mainly diminishing production of reactive oxygen species (ROS). It also can prevent DNA damage at physiological concentrations [8] .…”
Section: Introductionmentioning
confidence: 99%